2022
DOI: 10.3390/agronomy12081926
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomics to Explore the Bacteria Exo-Metabolome Related to Plant Biostimulants

Abstract: The control and development of plant growth promoters is a key factor for the agronomy industry in its economic performance. Different genera of bacteria are widely used as natural biostimulants with the aim of enhancing nutrition efficiency, abiotic stress tolerance and/or crop quality traits, regardless of their nutrients content. However, the complete exo-metabolome of the bacteria responsible for the biostimulant effect is still unknown and needs to be investigated. Three bacteria with different biostimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…A comparison of the functions of the identified metabolites revealed that endophytic PGPB was associated with diverse metabolic activities in sugarcane tissues, mainly carbohydrates and amino acids. The metabolic response of plants to inoculation with bacteria has been increasingly investigated in recent years, and few of those studies have analyzed the role of PGPB in shaping the tissue metabolome in carbon and N metabolism ( Garcia et al, 2022 ; Mhlongo et al, 2022 ). Amino acid metabolism is closely linked to carbohydrate and ammonium N (absorbed and synthesized from nitrate) metabolisms, which are the need for protein synthesis and secondary metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of the functions of the identified metabolites revealed that endophytic PGPB was associated with diverse metabolic activities in sugarcane tissues, mainly carbohydrates and amino acids. The metabolic response of plants to inoculation with bacteria has been increasingly investigated in recent years, and few of those studies have analyzed the role of PGPB in shaping the tissue metabolome in carbon and N metabolism ( Garcia et al, 2022 ; Mhlongo et al, 2022 ). Amino acid metabolism is closely linked to carbohydrate and ammonium N (absorbed and synthesized from nitrate) metabolisms, which are the need for protein synthesis and secondary metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…A metatranscriptomic study was conducted to investigate the contributions of different nitrogen-fixing bacteria present in the maize inoculated liquid ( Gomez-Godinez et al, 2018 ). Metabolomics was applied to explore the exo-metabolome of three PGPB ( Pseudomonas putida IDE-01, Azospirillum brasilense IDE-06, and Bacilus megaterium IDE-14) in interaction with maize and rice ( Garcia et al, 2022 ). No twodimentional study was found on gene expression and metabolome of salinity stress-alleviating PGPB in interaction with plants.…”
Section: Omics Methods For Assaying Molecular Mechanisms Of Pgpbmentioning
confidence: 99%
“…In bacteria, enzymes related to SA biosynthesis are encoded by the NRPS gene cluster. In first step which is common in both bacteria and plants, chorismate is converted to isochorismate by isochorismate synthase, and then SA is produced from isochorismate using isochorismate pyruvate lyase ( Chen et al, 2019 ; Mishra and Baek, 2021 ).The metabolites related to the auxins and zeatins biosynthesis pathways were explored from three PGPB ( Pseudomonas putida IDE-01, Azospirillum brasilense IDE-06, and Bacilus megaterium IDE-14) in interaction with maize and rice ( Garcia et al, 2022 ).…”
Section: Biochemical and Genetic Mechanisms Of Salinity Stress-allevi...mentioning
confidence: 99%
“…In potato, the transcriptional analysis of Burkholderia phytofirmans PsJN examined stress-activated genes that had an impact on transcriptional regulation, reactive oxygen reduction, and homeostasis [ 35 ]. In corn and rice individuals, metabolomics was used to reveal the exo-metabolome of strains functioning as PGPB ( Pseudomonas putida IDE-01, Azospirillum brasilense IDE-06 and Bacillus megaterium IDE-14) [ 36 ].…”
Section: Introductionmentioning
confidence: 99%